Development of rural areas through fiscal decentralization - Davydenko, Nadiia; Boiko, Svitlana; Buryak, Alina; Demianenko, Inna (My University, 2021)
The ratification of the European Charter of Local Self-Government and the adoption of the Concept of the Reform of Local Self-Government and the Territorial Organization of Power in Ukraine in April, 2014 laid the groundwork for the approval of fiscal decentralization and the creation of fiscal frameworks for the development of rural areas. One of the defining conditions of fiscal decentralization is the provision of the local government with financial resources in an amount sufficient to perform their tasks for development of rural areas. Therefore, the purpose of the article is to study the peculiarities of rural development of Ukraine in terms of fiscal decentralization, identify the main problems, and present an argument for the directions towards enhancing the positive impact of fiscal decentralization on the social and economic development of rural areas. The methodological basis of the article is general scientific and special methods of research, in particular: economic and statistical; analysis and synthesis; tabular and graphical. The conducted research has made it possible to establish that the implementation of fiscal decentralization has resulted in greater interest of village council in increasing revenues to local budgets by transferring the right to receive more tax revenues and non-tax revenues, finding contingency local budgets, improving the efficiency of tax administration and fees. The study gives grounds for proposing approaches to increase the effectiveness of fiscal decentralization in the context of rural development, including expanding of the list of taxes and fees in budget revenues of united territorial community (e.g. corporate income tax, personal income tax, environmental tax); improving the mechanism for providing local budgets with inter-budget transfers from the State Budget of Ukraine; optimization of budget expenditures under the condition that a guaranteed and affordable level of public services is provided; increasing the accountability of local governments in order to prevent corruption; involvement of the population in active participation in development policy of rural areas.
Keywords: decentralization; fiscal decentralization; united territorial communities; децентралізація; фіскальна децентралізація; об’єднані територіальні громади; кафедра фінансів